Fostering Democratic Citizenship: Innovative Approaches to Improve Civic Values in Elementary School Independent Curricula - Fitra, Nur Vania; Witanto, Yuli (MIMBAR PGSD Undiksha, 2024)
Indonesia highly upholds democratic values. Democracy is internalized since elementary education as the essence of Pancasila and Citizenship Education (PPKn). The purpose of this study was to analyze. Teachers' innovative approach strategies in implementing democratic values through PPKn subjects in the independent curriculum at the elementary school level. The researcher used a qualitative descriptive method. Data analysis includes four flows, namely data collection, data reduction, data presentation, and drawing conclusions. Data were collected through observation, interviews, and documentaries. The primary data source was the teacher, and the secondary data source was the fourth grade students. The results of the study showed that there were several approach strategies carried out in implementing democratic values in elementary schools, including: 1) the habit of shaking hands, 2) memorizing verses of the Quran and Asmaul Husna, 3) throwing garbage in its place, 4) school programs to involve teachers in scientific forums, 5) clean and healthy Fridays, 6) madrasah diniyah, 7) the habit of praying in congregation, and 8) visiting. In addition, teachers also insert democratic values in PPKn learning, such as: 1) group-based learning, 2) multicultural groups, 3) doing joint activities, 4) making democratic teaching modules. It is concluded that teachers have various innovative approach strategies to improve democratic citizenship values for students. The research findings provide valuable insights into innovative teacher approaches in integrating democratic values into Civic Education in elementary schools, which contribute to the development of scientific fields in promoting democratic citizenship.